A comparative study between continuous and interrupted sutures in open pyeloplasty. Issue 4 (November 2021) - Gupta, Sandeep; Verma, Ankit; Pal, Dilip Kumar
Background: Pelvi-ureteric junction obstruction (PUJO) is one of the common causes of obstructive uropathy dealt by urologists around the globe. The management of PUJO requires surgical intervention and pelvi-ureteral anastomosis is most time-consuming step in surgery and suturing plays a critical role for the good outcome of the surgery. Objective: To assess the outcomes of continuous or interrupted suturing in open pyeloplasties done for PUJ obstruction. Materials and methods: This comparative study was conducted in the department of Urology in a tertiary care hospital of eastern India. A total of 60 patients with pelviureteric junction obstruction were included as per inclusion and exclusion criteria and divided into two groups depending upon whether continuous (Group A) or interrupted (Group B) suturing was done. Both groups were compared for mean operative time, mean suturing time, duration of post-operative drainage, mean drain output, post-operative hospital stay, postoperative GFR and improvement in GFR. Results: Out of 60 patients continuous and interrupted suturing was done in 30 patients in both arms. Out of 60 cases there were 46 (76.66%) males and 14 (23.33%) females with a M:F ratio of 1:0.30. The mean age in group A and group B was found to be 30.06 ± 8.28 and 27.63 ± 6.07, respectively. Mean operative time, mean suturing time, duration of post-operative drainage, mean drain output and postoperative hospital stay were found to be higher in interrupted suture group and the difference was found to be statistically highly significant ( p  < 0.0001). The complication rates and recurrence rates were found comparable in both the cases with no statistically significant difference ( p  > 0.05). Conclusion: Continuous suturing technique for pyeloplasty is preferable as it is found to have a lower mean operative time, mean suturing time, duration of post-operative drainage, mean drain output and postoperative hospital stay.